COVID-19 and Entrepreneurship - Alina Sorgner (Institute of Labor Economics (IZA), 2023)
This chapter presents the results of a systematic review of literature (SLR) on impacts of Covid-19 on entrepreneurship published in the first three years since the outbreak of the Covid-19 pandemic, covering the period between January 2020 and January 2023. Main developments in the literature over time, space and themes are identified. The literature body has been growing constantly over time, with most studies included in this SLR published in 2022 that remained unconsidered in previous SLRs. In terms of spatial distribution of published research, a significant number of studies focus on North American and European countries, while low-income countries and countries in Latin American, Sub-Saharan and South Asian regions are underrepresented. Six main themes (and multiple sub-themes) were identified in the literature: entrepreneurial process, resilience and opportunity, entrepreneurial finance, policy responses to the Covid-19 crisis, gender, and well-being. Research on the impact the pandemic has had on entrepreneurial process, sources of financing, resilience of start-up firms, and opportunities emerging from the crisis has been dominating the literature since the early days of the pandemic and has been growing since then. Emerging themes include policy responses to the Covid-19 crisis and their (unintended) consequences for entrepreneurship, as well as differential impact of Covid-19 on female and male entrepreneurs. Studies on well-being of entrepreneurs, including their physical and mental health, represent a relatively low share of the literature on Covid-19 and entrepreneurship. Implications of the results for entrepreneurship research and practice are discussed.
Keywords: L26; 330; entrepreneurship; COVID-19; systematic literature review